PHYSICAL FEASIBILITY OF HYDRO-OCEANOGRAPHY FOR MARINE CULTURE WITH FLOATING NET CAGES ON THE EAST COAST OF PANGANDARAN - Firdaus, Muhamad Dadan; Gumilar, Iwang; Syamsuddin, Mega Laksmini; Pamungkas, Wahyuniar (Aqusains: Jurnal Ilmu Perikanan dan Sumberdaya Perairan, 2024)
This study aimed to analyze the physical feasibility of hydro-oceanography for marine culture business locations with floating net cages in the east coast area of Pangandaran, West Java. The method used in this study was a case study method with secondary data collected from satellite images and publication results. The results of this study showed that the location of the marine culture business with floating net cages on the east coast of Pangandaran is physically feasible for the cultivation of several commodities. Standard parameters for grouper culti-vation (Epinephelus sp.) are as follows: temperature 25-33 °C, salinity 20-35 ppt, pH 6.5-8.9, DO >4 mg/l, and ocean currents 10-75 cm/s. Standard parame-ters for lobster cultivation (Nephropi-dae) are conditionally: temperature 25-32 °C, salinity 25-37 ppt, pH 7.5-8.5, DO >4 mg/l, and ocean currents 5-100 cm/s. Standard aquatic parameters for barramundi cultivation (Lates calcarifer) are conditionally: temperature 26-32 °C, salinity 15-35 ppt, pH 7-8.5, DO >4 mg/l. Hydro-oceanographic parameter data from field measurements showed: temperature 27-30 °C, salinity 33-34 ppt, pH 7-8, DO 5.55-6.5 mg/l, and currents <100 cm/s. This means that hydro-oceanographic parameters for the marine culture on the East Coast of Pangandaran for lobster, grouper, and barramundi commodities are within the feasible category.  Keywords: Lobster culture, ocean data view, water qualty.